Manejo de cosecha y comercialización del cultivo de Palma Aceitera (Elaeis guineensis Jacq) en el Ecuador - Macías Cruz., Yoel Patricio (2021)
This research deals with the harvest management and commercialization of the Oil Palm (Elaeis guineensis Jacq) cultivation in Ecuador. In times of pandemic, this product was affected in terms of its harvest and commercialization, therefore it must be noted that all agriculture obtained unfavorable parameters at this time. Among the conclusions, it is detailed that the loose fruit must be collected at the moment of harvest and sent to the processing plant together with the bunches on the same day of harvest, this to avoid acidity; Harvesting is the most important, delicate and expensive operation in the production process, its main goal is to obtain the maximum amount of oil per hectare; The state of maturity of the fruit is considered as a good practical criterion of maturity, when the fruits of the bunch, in addition to presenting a color change from orange-red to opaque red; the transport of fruit from the harvesting platform (tambo) to the extractor must be carried out within 24 hours after the bunch cutting, the palm census specified that 57% of all the African palm plantations in Ecuador were affected by deadly phytosanitary problem and the pressure of prices has an international and national component, which have seen their production and inventories reduced in times of pandemic.